PENGEMBANGAN MEDIA PEMBELAJARAN KECEPATAN TENDANGAN PENCAK SILAT - Purnomo, Edi (Universitas Tanjungpura, 2020)
AbstractPencak Silat is a sport that is taught in schools, as a national culture that must be preserved. The results of kick learning in pencak silat learning in schools are usually used speed test instruments based on the lattice movements of pencak silat movements. In addition to tests that take the form of instrument tests, it can usually also be done by measuring the learning outcomes of pencak silat kick speed with a manual tool (stopwach). This tool has weaknesses in measurement. Usually there are deficiencies in turning on (on) and turning off (stop) the stopwach done by the tester. This deficiency can be helped by the development of the learning media of pencak silat kick speed. Development is done by designing the speed of pencak silat kicks with a microcontroller media that is coupled with a switch to start (on) and a switch to turn off (speed) the speed of pencak silat kicks. The research data of the development of learning media in the speed of pencak silat kicks was carried out from the material expert team at 82,5%, media experts at 90% and field trials at 92%. So the tool is feasible to use in the test results of learning speed pencak silat kicks.Keywords: Learning Media, Kick Speed, Pencak Silat